The contribution of graduation research to school development: graduation research as a boundary practice - Snoek, Marco; Bekebrede, Judith; Hanna, Fadie; Creton, Theun; Edzes, Hester (European Journal of Teacher Education, 2017)
When teaching is considered as a collaborative activity, the aim of research projects in schools needs to exceed the individual and personal levels and aim to contribute to research-informed reflection of a team of teachers. Within this multiple case study, we adapted the graduation research project within a primary teacher education programme, trying to bridge the personal level (where student-teachers show their individual competence) and the collaborative level (where the graduation research project aims to inspire practice of several teachers within a school). In this redesign of the graduation research project, the concepts of boundary activity, ownership, meaningfulness and dialogue were helpful. However, our study shows that connecting graduation research projects with school development is not just a matter of redesigning a part of the curriculum, but that it requires new perspectives and new qualities of student-teachers, research supervisors from the university and actors within the school.